Cognition and behaviour in frontotemporal dementia with and without amyotrophic lateral sclerosis. Issue 12 (14th October 2020) - Saxon, Jennifer A; Thompson, Jennifer C; Harris, Jennifer M; Richardson, Anna M; Langheinrich, Tobias; Rollinson, Sara; Pickering-Brown, Stuart; Chaouch, Amina; Ealing, John; Hamdalla, Hisham; Young, Carolyn A; Blackburn, Dan; et al.
Abstract : Objective: The precise relationship between frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) is incompletely understood. The association has been described as a continuum, yet data suggest that this may be an oversimplification. Direct comparisons between patients who have behavioural variant FTD (bvFTD) with and without ALS are rare. This prospective comparative study aimed to determine whether there are phenotypic differences in cognition and behaviour between patients with FTD-ALS and bvFTD alone. Methods: Patients with bvFTD or FTD-ALS and healthy controls underwent neuropsychological testing, focusing on language, executive functions and social cognition. Behavioural change was measured through caregiver interview. Blood samples were screened for known FTD genes. Results: 23 bvFTD, 20 FTD-ALS and 30 controls participated. On cognitive tests, highly significant differences were elicited between patients and controls, confirming the tests' sensitivities to FTD. bvFTD and FTD-ALS groups performed similarly, although with slightly greater difficulty in patients with ALS-FTD on category fluency and a sentence-ordering task that assesses grammar production. Patients with bvFTD demonstrated more widespread behavioural change, with more frequent disinhibition, impulsivity, loss of empathy and repetitive behaviours. Behaviour in FTD-ALS was dominated by apathy. The C9ORF72 repeat expansion was associated with poorer performance on language-related tasks. Conclusions: Differences were elicited in cognition and behaviour between bvFTD and FTD-ALS, and patients carrying the C9ORF72 repeat expansion. The findings, which raise the possibility of phenotypic variation between bvFTD and FTD-ALS, have clinical implications for early detection of FTD-ALS and theoretical implications for the nature of the relationship between FTD and ALS.